Investigation into the possibilty of producing organic controlled release fertilizers from oxidised coal - Tsatsi, William Letlape (My University, 2006)
Fertilizers are defined in the broadest sense as products that improve the levels of available plant nutrients or chemical and physical components that directly or indirectly enhance plant growth, yield and quality. The aim of this study was to produce slow controlled release fertilizers from oxidised coal. Two types of coals namely, Waterberg and Twistdraai (products, middlings) were utilised for the production of humic acids through slurry phase oxidation. The highest yields of humic acids were obtained in Waterberg and Twistdraai products samples. Subsequent to that, a nitrogen element was successfully inserted into the humic acid substrate. Humic acids are potential feedstock for modern manufacturing of organic fertilizers. The chemical substances regarded as hazardous to human consumption or those elements that negatively impact on the soil were significantly less detectable.
MSc (Eng) dissertation - Faculty of Engineering and the Built Environment
Keywords: fertilizers; plant nutrients; enhance plant growth; slow controlled release fertilizers; oxidised coal; Waterberg; Twistdraai; slurry phase oxidation